Underdevelopment of Left Atrial Appendage - Song, In Geol; Kim, Sung-Hwan; Oh, Yong-Seog; Rho, Tai-Ho (Korean circulation journal, 2017)
A patient was admitted for catheter ablation of atrial fibrillation. Cardiac computed tomography and transesophageal echocardiography revealed the absence of the left atrial appendage. However, the right atrial appendage looked normal and the level of pro B-natriuretic peptide was within normal limits. Successful catheter ablation was performed without any procedural complications and the sinus rhythm was appropriately maintained for 10 months with an antiarrhythmic drug.